2015
DOI: 10.1007/s13197-015-1764-9
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer simulation and retort program adjustment for thermal processing of wheat based Haleem in semi-rigid aluminum containers

Abstract: A mixed computational strategy was used to simulate and optimize the thermal processing of Haleem, an ancient eastern food, in semi-rigid aluminum containers. Average temperature values of the experiments showed no significant difference (α = 0.05) in contrast to the predicted temperatures at the same positions. According to the model, the slowest heating zone was located in geometrical center of the container. The container geometrical center F0 was estimated to be 23.8 min. A 19 min processing time interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The SHZ developed into an ellipse shape after a short period of heating (Ghani et al 2002a, b). Vatankhah et al (2015) indicated that SHZ for semi-rigid containers containing…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SHZ developed into an ellipse shape after a short period of heating (Ghani et al 2002a, b). Vatankhah et al (2015) indicated that SHZ for semi-rigid containers containing…”
Section: Resultsmentioning
confidence: 99%
“…Since the semi-rigid aluminum packaging has recently been introduced to the market, there is limited information about the temperature distribution during the heating process of such containers. Vatankhah et al (2015) carried out a heat transfer simulation and retort program adjustment for thermal processing of a wheat-based food in semi-rigid aluminum containers. However, no study has addressed heat transfer in thermal pasteurization processes in semirigid aluminum containers filled with apple puree.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because of the lower heat capacity of air in the headspace. Another important factor disturbing an accurate prediction of the simulation model is the structural changes of the food, such as setting of starch and protein denaturation [61]. The heat transfer simulation model for fish myofibrillar protein paste was developed by Lee and Yoon [62].…”
Section: Solid and Very Viscous Foodsmentioning
confidence: 99%
“…Headspace in canned liquid foods has significant effects on the heat transfer during the sterilization process [44,70]. In contrast to the study on the effect of headspace for canned solid food, headspace in canned liquid food results in a faster heating rate compared to its rate without headspace, which is mainly due to the natural convection of fluid in canned liquid foods [61,70]. In the canning industry, rotary processing during sterilization has recently been widely used, and these processes significantly speed up the sterilization process.…”
Section: Liquid Foodsmentioning
confidence: 99%
See 1 more Smart Citation